2017
DOI: 10.1038/s41467-017-01885-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacological inhibition of microRNA-92a maintains podocyte cell cycle quiescence and limits crescentic glomerulonephritis

Abstract: Crescentic rapidly progressive glomerulonephritis (RPGN) represents the most aggressive form of acquired glomerular disease. While most therapeutic approaches involve potentially toxic immunosuppressive strategies, the pathophysiology remains incompletely understood. Podocytes are glomerular epithelial cells that are normally growth-arrested because of the expression of cyclin-dependent kinase (CDK) inhibitors. An exception is in RPGN where podocytes undergo a deregulation of their differentiated phenotype and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 68 publications
3
45
0
1
Order By: Relevance
“…Functional studies have shown that microRNA dysregulation is causal in myriad diseases, with microRNAs acting as activators or suppressors, and insight into the roles of microRNAs in disease progression has made microRNAs attractive targets of therapeutic modalities [96][97][98][99]. Here, we only highlight microRNA-21, -205 and -153 that play pivotal roles in renal disorders.…”
Section: Micrornasmentioning
confidence: 98%
“…Functional studies have shown that microRNA dysregulation is causal in myriad diseases, with microRNAs acting as activators or suppressors, and insight into the roles of microRNAs in disease progression has made microRNAs attractive targets of therapeutic modalities [96][97][98][99]. Here, we only highlight microRNA-21, -205 and -153 that play pivotal roles in renal disorders.…”
Section: Micrornasmentioning
confidence: 98%
“…The activity of specific miRNAs in the kidney may be modulated by in vivo delivery of mimics that restore miRNA levels or inhibitors that block miRNA function. Successful kidney transfection has been achieved by intraperitoneal, intravenous, or subcutaneous injection of either mimics or inhibitors [105,106]. Therefore, miRNA regulation has been proposed as a promising therapeutic target for DN [107,108].…”
Section: Micrornas In Diabetic Nephropathymentioning
confidence: 99%
“…9 Crescentic nephritis, characterized by the rapid formation of extracapillary hypercellular lesions (crescents), is one of the most aggressive forms of kidney disease. 10 Current therapies are based on nonspecific immunosuppression, as immune cells are thought to mediate disease development and progression. 11 Importantly, recent evidence suggests that glomerular crescent formation involves also nonimmune cells, namely glomerular visceral epithelial cells (podocytes) 10 and parietal epithelial cells (PECs), 12 and interstitial fibrosis.…”
mentioning
confidence: 99%